You are on page 1of 22

# 2

--
--

21

x(t)

x(t)
M

x0
o

x (t ) = A cos
t + 0
m

x0 cos( 0t + 0 )

<page break>
22

x(t ) = x(t + T ) = x(t + 2T ) = = x(t + nT )
(n = 1 2
)

Tn

n =1

n=1,

2, 3

1
a0 =
T
2
an =
T
bn =

2
T

T
2

T
2

T
2

x(t )dt

x(t ) sin n 0tdt

-- 0--, 0=2 /T

## x(t ) = a0 + An cos( n0t + n )

n =1

An = an2 + bn2
bn
n = arctg
an
n = 1, 2, 3,

--

An

0 20 30 40

0 20

x(t)

-A

2
0 =
T

a 0 = a n = 0
t
T

2 2
bn = T x(t ) sin n 0tdt
T 2

4 T2
2A
= A sin n 0tdt =
[
1 cos n ]
T 0
n
4A

n
= n
0 n
n

4A

An = a + b = bn =
n =

n
2
( n = 1,3,5, )
2
n

2
n

4A

## x(t ) = cos( n0t )

2
n n

( n =1,3,5, )

4A
An 4A

4A
3 5

3 0

5 0

e j t = cos t j sin t

1 j t

j t
cos

t
=
(
e
+
e
)

j
sin t = ( e jt e jt )
2

j = 1

x (t ) =

jn0 t
c
e
n

( n = 0, 1, 2, 3,)

n =

1
c0 = a0 =
T

T
2
T

x(t ) dt

an jbn
cn =
2
1 T2
= T x(t )e jn0t dt
T 2
anbn
n
cn
annbnn

#
an = an

bn = bn

cnc-n
cn

cn = cn e jn

cn = cn

n = n

cnc-n

n>0
a n2 + (bn ) 2 An
cn =
=
2
2

bn
n = arctg
an

An
cn =
2

bn
bn
= arctg
= arctg
an
an

cn
:|cn|- :
n-

An

A1

cn

A2

0 2 0
n

2
0 2 0
1

A1
c1 =
2

c2 =

0 2 0
1 1n
2 0
2

0
1

:Recn-
Imcn- an- -bn- .
#

2
2 0

<page break>

23

a.

b.
x(t)

x(t)

x(t)

2.222.16

x(t)X( )
1
j t
x (t ) =
x
(
t
)
e
dt

e j t d

x(t)X()

X () = x(t ) e j t dt

X()x(t):

1
x (t ) =
2

X ( )e jt d

1
X ()e jt d
2
X( )x(t)

1
j t
jn 0 t
[
]
X
(

)
d

c
e
n
2

X( )x(t)
X( )

X () = X () e j()
f (Hz)f =w/
(2p)
X(f)=

x ( t )e j 2

f t

dt

x ( t ) = X ( f ) e j 2 f t df

X( f )
X ( f ) = X ( f ) e j( f )

( )

X ( )

ReX()Im()
X( )X( )
X( )

FT
a1 x1 (t ) + a 2 x2 (t )
a1 X 1 ( f ) + a 2 X 2 ( f )

FT
X (t )
x( f )

FT
x(t t 0 )
X ( f )e j 2 f t 0

f 2 ft0

FT
x(t )e j 2 ft 0
X ( f f0 )

1
f
x (at ) = X ( )
a
a

d n x(t ) FT
n

(
j
2

f
)
X( f)
n
dt

x(t ) y (t ) = x( ) y(t )d

FT
x(t ) y(t )
X ( f )Y ( f )
FT
x(t ) y (t )
X ( f ) Y ( f )

x(t)
x(t)

(t )

1/
- /2 /2

t
A

A (t t0 )

t0

t = 0
(t ) =
0 t 0

( t ) dt = 1

1
x (t 0 ) (t t 0 )
(t t 0 )
(t )
x(t)
x ( 0) ( t )
x(t)

t0

t = 0
x(t ) (t t0 ) =
0 t 0

## x(t ) (t t 0 )dt = x(t 0 ) (t t 0 ) dt = x(t 0 )

1.
x(t)
2.

2
(a) 2

x(t ) (t ) = x( ) (t )d

= x(t ) (t ) d

= x (t )

(b) 2

x(t ) (t t0 ) = x( ) (t t0 ) d

= x(t t0 ) (t t0 ) d

= x(t t0 )

x(t)

(t t0 )

t0

x(t t 0 )

(t ) ( f ) = (t )e j 2 ft dt = 1
FT

3
FT
(t t 0 )
e j 2 ft

FT
1
( f ) = ( f )

FT
e j 2 f 0 t
( f f 0 )

cos 2 ft
1
1
1
FT
= e j 2 ft + e j 2 ft
( f + f 0 ) + ( f f 0
2
2
2

sin 2 ft
=

j j 2 ft
j
j
FT
e
e j 2 ft
( f + f 0 ) ( f f 0
2
2
2

(f)

1/2
-f0

(f)

1/2
f0

1/2

f0

-f0

f
-1/2

<page break>